The Living Conditions of Children - Patrinos, Harry Anthony (The World Bank, 2007)
This paper summarizes the socioeconomic conditions of children around the world. It explores solutions to the main problems, along with a summary of the costs and benefits of some of the solutions. Emphasis is on the results from rigorous studies, impact evaluations, and randomized experiments. Although the cost-evidence literature is scarce, a good case for early interventions and key quality-enhancing education interventions exists